P-82 Let's talk about it; optimising the advance care directive process. (1st September 2015) - Cairney, H; Billings, S; Kinsella, C; Austin, N; Hunter, P
Abstract : Background: The completion of Advance Care Directives (ACDs) continues to be a challenge in Australia with studies in Victoria revealing low numbers of completed ACDs and lack of quality information to assist loved ones in making appropriate choices. Aim: To compare the level of agreement in different scenarios between community dwelling seniors (consumers) and their substitute decision makers (SDMs) in completing a person or patient-based ACD and whether the information included changes following discussions with a clinician and the SDM. Methods: 60 consumers were recruited and randomly allocated to complete one of two ACDs. These ACDs were provided to the consumer's SDM to assist in making a treatment decision that would best replicate the consumer's wishes in three medical scenarios of increasing uncertainty. The ACD and the results of the scenario testing were then discussed with the consumer, SDM and Advance Care Planning clinician. Consumers were then invited to complete a second ACD. Results: Overall consumer-SDM agreement declined as the scenario became more uncertain. Following the scenario testing, the majority of consumers made changes to the directive. Responses were more consistent for values based questions compared to questions relating to medical treatments with new concepts and treatment ideas included in the second version. Discussion/conclusion: In order to meet the growing demands for ACP in the community, individuals should be encouraged to have conversations with families and loved ones about their values and preferences for quality of life and supported by clinicians to have discussions around preferences, particularly for medical treatment.